pH-sensitive and biodegradable charge-transfer nanocomplex for second near-infrared photoacoustic tumor imaging - Wang, Zhimin (2018)
The emerging photoacoustic imaging (PAI), especially in the NIR window, offers reliable sensing for deep-penetration and high-resolution closing to clinical requirements. However, the contrast agents that are capable of specifically responding to the intricate biological environments, more importantly, indicate promising biodegradability and biocompatibility are still limited. Herein, we introduce a new class of pH-sensitive organic PA contrast agent working in the second near-infrared window (NIR-II, 960 - 1700 nm), which is derived from the self-assembled charge-transfer nanocomplex (CTN) by 3, 3’, 5, 5’-tetramethylbenzidine (TMB) and its dication structure (TMB++). Such unique NIR-II-responsive CTN can specifically respond to pH change in the physiological range, allows noninvasive and sensitive visualization of the tumor acidic microenvironment (e.g. at pH 5) in mice with higher signal-to-noise ratio (SNR). Moreover, this organic CTN demonstrates the biodegradable feature in physiological condition (e.g. at pH 7.4), which provides the great biosafety without the concern of nanoparticles accumulation in vivo. These results clearly show the potential of TMB/TMB++-based CTN as a promising pH-activatable and biodegradable molecular probe for specific tumor photoacoustic imaging in the NIR-II region.